Solution-processed near-infrared Cu(In,Ga)(S,Se)(2) photodetectors with enhanced chalcopyrite crystallization and bandgap grading structure via potassium incorporation - Kim, Joo-Hyun; Han, Hyemi; Kim, Min Kyu; Ahn, Jongtae; Hwang, Do Kyung; Shin, Tae Joo; Min, Byoung Koun; Lim, Jung Ah (Nature Publishing Group, 2021)
Although solution-processed Cu(In,Ga)(S,Se)2 (CIGS) absorber layers can potentially enable the low-cost and large-area production of highly stable electronic devices, they have rarely been applied in photodetector applications. In this work, we present a near-infrared photodetector functioning at 980 nm based on solution-processed CIGS with a potassium-induced bandgap grading structure and chalcopyrite grain growth. The incorporation of potassium in the CIGS film promotes Se uptake in the bulk of the film during the chalcogenization process, resulting in a bandgap grading structure with a wide space charge region that allows improved light absorption in the near-infrared region and charge carrier separation. Also, increasing the Se penetration in the potassium-incorporated CIGS film leads to the enhancement of chalcopyrite crystalline grain growth, increasing charge carrier mobility. Under the reverse bias condition, associated with hole tunneling from the ZnO interlayer, the increasing carrier mobility of potassium-incorporated CIGS photodetector improved photosensitivity and particularly external quantum efficiency more than 100% at low light intensity. The responsivity and detectivity of the potassium-incorporated CIGS photodetector reach 1.87 A W−1 and 6.45 1010 Jones, respectively, and the − 3 dB bandwidth of the device extends to 10.5 kHz under 980 nm near-infrared light.